Disfungsi Relasi Pemerintah dan Masyarakat dalam Penanganan Pascabencana Semeru: Perspektif Ekologi Pemerintahan - Thabita Clarista Rahmania Oktaf; Baktiawan Nusanto (Jurnal Ragam Pengabdian, 2026)
The eruption of Mount Semeru in December 2021 not only left massive physical destruction but also exposed fundamental weaknesses in post-disaster governance in Indonesia. This article examines the dysfunction of relations between the government and society in the post-disaster management of Semeru, employing a governance ecology analytical framework. The study aims to identify the forms of relational dysfunction, trace the ecological factors driving such dysfunction, and analyze its implications for overall post-disaster governance effectiveness. The method used is qualitative-descriptive, based on systematic literature review with source triangulation from official government reports, scientific publications, and field documentation from various institutions. Findings reveal that relational dysfunction manifests in three main dimensions: fragmentation of inter-level government communication, marginalization of community participation in decision-making, and misalignment between rehabilitation policies and the actual needs of affected residents. Ecologically, this dysfunction is driven by the misalignment between formal bureaucratic structures and dynamic local social ecosystems, weak adaptive capacity of governance actors, and the absence of an inclusive and equitable collaboration platform. These findings contribute to the development of governance ecology theory in the context of disasters, while offering policy recommendations to strengthen government-community synergy in future emergency management.